2017
DOI: 10.7324/japs.2017.70118
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of permanganate oxidation of nalidixic acid in aqueous alkaline medium

Abstract: The kinetics and mechanism of oxidation of nalidixic acid (NA) by permanganate ion in alkaline medium have been studied at 40 ± 1 o C. The Stoichiometry was observed to be 2:1 in terms of mole ratio of permanganate ion and nalidixic acid consumed. The reaction shows first order with respect to oxidant and fractional order in both the substrate and alkali concentration. The oxidation reaction proceeds via an alkali permanganate species that forms a complex with nalidixic acid and the complex then decomposes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The double reciprocal plot between (kobs) -1 and [CIP] -1 was made from Equation (6) that yield a straight line with non-zero intercept (R 2 = 0.999) ( Figure 10). The value of 'k' to be 1.40×10 -3 , 1.90×10 -3 , 2.44×10 -3 /s -1 from intercepts and value of 'K' to be 10.5×10 2 , 15.2×10 2 , 20.7×10 2 /dm 3 .mol -1 from the ratio of intercept [51]. The value of entropy of activation (ΔS) = -92.27 JK -1 mol -1 express the formation of intermediate complex and such an activated complex is more ordered than the reactants due to loss of degree of freedom.…”
Section: Mechanismmentioning
confidence: 99%
“…The double reciprocal plot between (kobs) -1 and [CIP] -1 was made from Equation (6) that yield a straight line with non-zero intercept (R 2 = 0.999) ( Figure 10). The value of 'k' to be 1.40×10 -3 , 1.90×10 -3 , 2.44×10 -3 /s -1 from intercepts and value of 'K' to be 10.5×10 2 , 15.2×10 2 , 20.7×10 2 /dm 3 .mol -1 from the ratio of intercept [51]. The value of entropy of activation (ΔS) = -92.27 JK -1 mol -1 express the formation of intermediate complex and such an activated complex is more ordered than the reactants due to loss of degree of freedom.…”
Section: Mechanismmentioning
confidence: 99%
“…Products of photodegradation and oxidization of KMnO 4 in a strongly acidic medium. [ 31–33 ] X = C–H in NF and CF and C‐alkoxy (a methyl‐substituted oxyethylene bridge between the nitrogen atom and position C8) in OF; R 1 = ethyl group in NF, cyclopropyl group in CF; R 2 = piperazinyl ring in NF and CF and methyl piperazinyl derivative in OF…”
Section: Resultsmentioning
confidence: 99%
“…HCF is a transition metal complex, consisting of a central iron ion, surrounded by six negative cyanide ions, or ligands, in an octahedral arrangement. A literature survey revealed that the kinetics and mechanism of oxidation of CIP by different oxidants such as ClO 2 , ozone‐free chlorine, and permanganate was carried out in both acidic and alkaline medium . However, the reaction of CIP with HCF has not been investigated in detail and thus is the focus of this study, and title reaction is undertaken to understand the mechanism of the reaction and active species involved in the Cu(II)‐catalyzed reaction.…”
Section: Introductionmentioning
confidence: 99%